Teacher Strategies for Improving the Ability to Read the Qur'an in Early Childhood - Holidah, Nur; Masrurah, Waqiatul; Iftitah, Selfi Lailiyatul (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2022)
This study aims to describe the teaching strategies used by teachers when learning the Qur'an in early childhood in a kindergarten in Pamekasan regency, East Java. What are the obstacles faced by teachers at the time of learning the Qur'an? How do teachers overcome the obstacles of teaching in early childhood? This study uses a descriptive qualitative approach, in which sources are obtained through interviews, observation, and documentation. As for the informant principal and class, the teacher checks the validity of the data through continuous observation, extending the observation, and triangulation. The study's results showed that: first, at the design stage, the teacher is required to make the RPPH. After that, the teacher checks the student's presence one by one, motivates children, and gives a stimulus to their students. Second is the implementation. There are some things that teachers and students must do before learning, such as reading prayers, reading short surah using the iqro' method, starting with taawudz, using fingers for the short length of a reading, reading with tahqiq, tartil, and tajweed. The third is the evaluation. The teacher does several ways, such as holding a test and giving a star symbol for appreciation. Based on the results of the study, it can be concluded that the strategy of teachers in improving the ability to read the Qur'an in early childhood is, using several stages the first, the design stage, the second stage of implementation, and the third stage of evaluation. These three stages are carried out in the learning process. Abstrak Penelitian ini bertujuan untuk mendeskripsikan strategi mengajar yang digunakan guru pada saat pembelajaran Al-Qur’an pada anak usia dini di sebuah taman kanak-kanak di kabupaten Pamekasan, Jawa Timur. Apa saja kendala yang dihadapi oleh guru pada saat pembelajaran Al-Qur’an? Bagaimana cara guru dalam mengatasi kendala mengajarnya pada anak usia dini? Penelitian ini menggunakan pendekatan kualitatif deskriptif, di mana sumber yang diperoleh melalui wawancara, observasi, dan dokumentasi. Adapun yang menjadi informan kepala sekolah dan guru kelas, untuk pengecekan keabsahan data melalui pengamatan terus-menerus, memperpanjang masa observasi dan triangulasi. Hasil dari penelitian menunjukkan bahwa: Pertama, pada tahap rancangan guru diwajibkan membuat RPPH setelah itu mengabsen satu persatu, dan memberi sebuah motivasi pada anak dan memberi sebuah ransangan pada anak didiknya. Kedua, pada ahap pelaksanaan yaitu ada beberapa yang harus guru laksanakan ketika tahap pelaksanaan yaitu membaca doa sebelum belajar, membaca surat-surat pendek, menggunakan metode iqro’, memulai dengan taawudz, menggunakan jari untuk panjang pendeknya suatu bacaan, membaca dengan tahqiq, membaca dengan tartil, membaca dengan menggunakan tajwid. Ketiga, pada tahap evaluasi guru melakukan beberapa cara, caranya adalah mengadakan tes dan pemberian simbol bintang. Berdasarkan hasil penelitian dapat disimpulkan bahwa strategi guru dalam meningkatkan kemampuan membaca Al-Qur’an anak usia dini yaitu, menggunakan beberapa tahap yang pertama, tahap rancangan, yang kedua tahap pelaksanaan, yang ketiga tahap evaluasi. Ketiga tahap ini dilakukan dalam proses pembelajaran.